Genetics of subcortical vascular dementia - Schmidt, Helena (Elsevier Science, 2012)
Subcortical vascular dementia or cerebral small vessel disease is a common cause of disability in the elderly. On magnetic resonance imaging the disease is manifested as white matter lesions, lacunes and microbleeds. Its etiology is complex, with age and hypertension as established risk factors. The heritability of white matter lesions is constantly high over different populations. Linkage studies identified several loci for these lesions however no genes responsible for the linkage signals had been identified so far. Results from genetic association studies using the candidate gene approach support the role of APOE, the renin–angiotensin system, as well as the Notch3 signaling pathway in the development of subcortical vascular dementia. The recent genomegenome wide association study on white matter lesions identified a novel locus on chromosome 17q25 harboring several genes such as TRIM65 and TRIM47 which pinpoints to possible novel mechanisms leading to these lesions.